Structural and Material Properties of Chitin Nanofibers Produced Without Deacetylation Treatment - Yuka Tomita; Tomohito Yagita; Yuto Kaku; Tsuguyuki Saito; Shuji Fujisawa (Nano Select)
ABSTRACT Deacetylation pretreatment is commonly applied to chitin nanofibers to introduce positive charges on their surface, increasing their fibrillation efficiency in water. However, without this treatment, chitin cannot be easily disintegrated into fibers with widths of several nanometers. Here, we developed chitin nanofibers from crab shells without deacetylation treatment. The chitin nanofibers had an average width of 6.5 nm, a length of several micrometers, and good colloidal stability in water. The nanofibers formed more stable Pickering emulsions than did the deacetylated chitin nanofibers because of better adsorption at the water–oil interface. Even though the strength and toughness of the chitin nanofiber films were inferior to those of the films of the deacetylated chitin nanofibers, the chitin nanofibers possessed unique optical properties, combining high transparency and high haze, which was not observed in the deacetylated chitin nanofiber film. These characteristics indicate that the use of chitin nanofibers without deacetylation treatment could expand the range of material properties available for chitin‐based materials, providing new avenues for controlling material properties. Our research highlights the potential of using chitin nanofibers in the development of green, high‐performance materials for applications in cosmetics and optics, contributing valuable insights into the sustainable utilization of chitin‐based nanofibers.